Digital challenges in environmental education (Training and Practice : Journal of Educational Sciences, 2018)
Education in the 21st century is unimaginable without the innovative application of technological developments. The way of cognition, understanding and learning affects the future applicability of knowledge, competences. In lower elementary schools, the environment-related content may be used most effectively when all senses are involved in the acquisition according to the content of  the knowledge and it reaches  the most efficient channel or combination of channels until logical processing. Therefore, when applying digital tools the following circumstances are to be considered:- Technological tools can make the teaching of environmental education more effective,- They cannot be used efficiently in every moment of the lesson,- Their application is limited by socio-economic opportunities,- Creative educators can demonstrate dangerous or costly interactions without digital tools.